1995
DOI: 10.1007/bf00180947
|View full text |Cite
|
Sign up to set email alerts
|

Serum-induced collagen gel contraction

Abstract: Gel electrophoresis revealed a new high-molecular-weight band (M(r) 240,000) presumably due to intermolecular cross-links of collagen peptides and FN. The serum components also were shown to cause a significant decrease in the volume of the collagen gel. CONCLUSION. Collagen gel contraction could be attributed to the collagen-FN-collagen cross-links catalyzed by TG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Serum-induced collagen contraction may also contribute to contraction of the vitreous cortex in diabetes [24].…”
Section: Discussionmentioning
confidence: 99%
“…Serum-induced collagen contraction may also contribute to contraction of the vitreous cortex in diabetes [24].…”
Section: Discussionmentioning
confidence: 99%
“…In this model, fibroblasts can reach a high degree of differentiation, exhibiting a bipolar morphology, controlled cell division, and regulated synthesis of macromolecules. Reorganization of the collagen gels by fibroblasts propagated throughout the interconnected collagen's fibril network (10). Previous studies have shown that DNA synthesis and collagen synthesis by fibroblasts decreased after contraction of collagen gel (11).…”
mentioning
confidence: 94%
“…After an eye injury, the intraocular structures change, and the blood-retinal barrier is broken. The blood components and cell mediation lead to vitreous shrinkage, causing PVD [22–24]. Therefore, with a greater delay in performing vitrectomy after the injury, fewer vitreous remnants remain.…”
Section: Discussionmentioning
confidence: 99%